(untitled) - 1962-; Loupy, Christophe; Tharlet, Eve.; James, J. Alison (New York, 2001)
Hugs the puppy sets out to collect lots of wonderful kisses from his animal friends, but in the end he discovers that the best kiss of all is the one he gets from his loving mother.
"A Michael Neugebauer book."
Keywords: Kissing; Fiction; Dogs; Fiction; Animals; Fiction; Mother and child; Fiction